Diagnosis of Prenatal-Onset Achondrogenesis Type II by a Multidisciplinary Assessment: A Retrospective Study of 2 Cases - Wenbo Wang; Qichang Wu; Li Sun; Xiaohong Zhong; Yasong Xu; Xiaojian Xie; Zhiying Su (Case Reports in Obstetrics and Gynecology)
Aim. Achondrogenesis type II is a rare, lethal osteochondrodysplasia with considerable phenotypic heterogeneity. We describe our experience in diagnosing prenatal-onset achondrogenesis type II by a multidisciplinary assessment. Methods. Two cases of fetal achondrogenesis type II were analyzed retrospectively using prenatal ultrasound evaluation, postnatal radiographic diagnosis, and molecular genetic testing of COL2A1. Results. A causative mutation in the COL2A1 gene was found in both patients. Combined with postnatal radiographic examination, the final diagnosis of achondrogenesis type II was made. Conclusion. Our findings emphasize the importance of a multidisciplinary assessment for the definitive diagnosis of achondrogenesis type II, which is paramount for proper genetic counseling.